Retraction Notice for "Age Estimation from Ossification of Clavicle: A Comprehensive Review" - Rahman, Md. Rezwanur (Delta Medical College Journal, 2017)
On 17th May 2017 the Editorial Board of Delta Medical College Journal agreed to retract the article 'Age Estimation from Ossification of Clavicle: A Comprehensive Review' published in Delta Medical College Journal, Vol.4(2) pages 89-96 (DOI: http://dx.doi.org/10.3329/dmcj.v4i2.29381) as it was found to contain an extensive overlap of text sections from the following published article: 'Estimation of age from ossification of clavicle: A Comprehensive Review' published in the Journal of Indian Academy of Forensic Medicine, Vol.31(3) pages 277-284. http://medind.nic.in/jal/t09/i3/jalt09i3p277.pdf